Atherogenic properties of lipoproteins in HIV patients starting atazanavir/ritonavir or darunavir/ritonavir: a substudy of the ATADAR randomized study. (23rd December 2014) - Saumoy, Maria; Ordóñez-Llanos, Jordi; Martínez, Esteban; Ferrer, Elena; Domingo, Pere; Ribera, Esteban; Negredo, Eugenia; Curto, Jordi; Sánchez-Quesada, José Luis; Di Yacovo, Silvana; González-Cordón, Ana; Podzamczer, Daniel
Abstract: Objectives: To assess LDL subfraction phenotype and lipoprotein-associated phospholipase A2 (Lp-PLA2) in naive HIV-infected patients starting atazanavir/ritonavir or darunavir/ritonavir plus tenofovir/emtricitabine. Methods: This was a substudy of a multicentre randomized study. Standard lipid parameters, LDL subfraction phenotype (by gradient gel electrophoresis) and Lp-PLA2 activity (by 2-thio-PAF) were measured at baseline and weeks 24 and 48. Multivariate regression analysis was performed. Results are expressed as the median (IQR). Results: Eighty-six (atazanavir/ritonavir, n = 45; darunavir/ritonavir, n = 41) patients were included: age 36 (31–41) years; 89% men; CD4 319 (183–425) cells/mm 3 ; and Framingham score 1% (0%–2%). No differences in demographics or lipid measurements were found at baseline. At week 48, a mild but significant increase in total cholesterol and HDL-cholesterol was observed in both arms, whereas LDL cholesterol increased only in the darunavir/ritonavir arm and triglycerides only in the atazanavir/ritonavir arm. The apolipoprotein A-I/apolipoprotein B ratio increased only in the atazanavir/ritonavir arm. At week 48, the LDL subfraction phenotype improved in the darunavir/ritonavir arm (increase in LDL particle size and in large LDL particles), whereas it worsened in the atazanavir/ritonavir arm (increase in small and dense LDL particles, shift to a greater prevalence of phenotype B); the worsening was related to the greater increase in triglycerides in the atazanavir/ritonavir arm. No changes in total Lp-PLA2 activity or relative distribution in LDL or HDL particles were found at week 48 in either arm. Conclusions: In contrast with what occurred in the atazanavir/ritonavir arm, the LDL subfraction phenotype improved with darunavir/ritonavir at week 48. This difference was associated with a lower impact on plasma triglycerides with darunavir/ritonavir.